Characterizing the Statistical Properties of SAR Clutter by Using an Empirical Distribution - Gui Gao; Gongtao Shi; Huanxin Zou; Shilin Zhou (International Journal of Antennas and Propagation)
The performances on the applications of synthetic aperture radar (SAR) data strongly depend on the statistical characteristics of the pixel amplitudes or intensities. In this paper, a new empirical model, called simply ℋ𝒢o, has been proposed to characterize the statistical properties of SAR clutter data over the wide range of homogeneous, heterogeneous, and extremely heterogeneous returns of terrain classes. A particular case of the ℋ𝒢odistribution is the well-known 𝒢o distributions. We also derived analytically the estimators of the presented ℋ𝒢o model by applying the “method of log cumulants” (MoLCs). The performance of the proposed model is verified by using some measured SAR images.